Results 1 to 1 of 1

Thread: sdf

  1. #1
    Junior Member
    Joined
    Oct 2007
    From
    Bath, UK
    Posts
    25

    sdf

    $\displaystyle s^*=(1-H)(1+R(1-\frac{s^*}{K}))=s^*$

    $\displaystyle 1=(1-H)(1+R(1-\frac{s^*}{K}))1$

    $\displaystyle \frac{1}{1-H}-1=R(1-\frac{s^*}{K})$

    $\displaystyle \frac{1}{R} * \frac{1}{1-H}-1=1-\frac{s^*}{K}$

    $\displaystyle s^* = K - \frac{K}{R(1-H)} + \frac{K}{R}$

    Edit: Sorry, I'm just using this to do a test. I meant to preview this.
    Last edited by bumcheekcity; Mar 5th 2009 at 09:48 AM. Reason: Oops!
    Follow Math Help Forum on Facebook and Google+

Search Tags


/mathhelpforum @mathhelpforum